Molecular Basis of Hurthle Cell Papillary Thyroid Carcinoma1 - Carol C. Cheung; Shereen Ezzat; Lily Ramyar; Jeremy L. Freeman; L. Sylvia (2000)
Among thyroid neoplasms, Hurthle cell tumors (HCTs) have traditionally been a distinct diagnostic category. Hurthle cell adenomas are encapsulated follicular lesions with benign behavior. Hurthle cell carcinomas exhibit unequivocal capsular and/or vascular invasion; they are aggressive tumors with a poor prognosis. Recently, Hurthle cell papillary thyroid carcinomas (PTCs) have been identified on morphological grounds. We hypothesize that a subset of HCTs represent PTC with clinical, histological, and immunohistochemical features based on specific molecular events. ret/PTC gene rearrangements give rise to novel oncogenes that are unique to PTC. We studied a group (n = 50) of HCTs for ret/PTC gene rearrangements. Tumors were examined for papillary differentiation by light microscopic evaluation of nuclear features, by RT-PCR for ret/PTC gene rearrangements, and by immunohistochemistry for ret. Among 24 noninvasive tumors, 13 contained ribonucleic acid for ret/PTC-1, -2, or –3, and 9 of these were immunoreactive for ret. Among 19 Hurthle cell carcinomas, 15 had focal nuclear hypochromasia with grooves and/or inclusions; expressed transcripts of ret/PTC-1, -2, or –3; and exhibited ret positivity. Tumors with ret/PTC gene rearrangements tended to have lymph node metastases rather than hematogenous spread. Our results indicate that a subset of HCTs exhibit features of PTC that are attributable to specific gene rearrangements, resulting in expression of ret/PTC oncogenes. These data support subclassification of HCTs into three groups: Hurthle cell adenomas, Hurthle cell carcinomas, and Hurthle cell PTC.